A Proof-of-Concept Study of Game-Based Learning in Higher Education. (August 2016) - Crocco, Francesco; Offenholley, Kathleen; Hernandez, Carlos
Background . Much literature has theorized on the potential educational benefits offered bygame-based learning (GBL). However, recentmeta-data analyses of studies conducted on the efficacy ofGBL offermixed results . Furthermore, many of the studies available rely more on close reading, inference, small sample sizes, and qualitative responses than on quantitative, data-driven analyses. Aim . This article describes a proof-of-concept study designed to assess theeffects ofGBL onenjoyment, engagement, andlearning inhigher education using a large sample size and quantitative measures. Method . The study uses a large data set (n = 440) involvingEnglish, Math andScience undergraduate courses. For the first semester, faculty participants were trained in how to implementgame-based pedagogy and created analoggame-based lessons. In the following semester, each professor taught one section of a course usinggames and another section of the same course withoutgames . Students in the game-based and control groups were givenattitude surveys about the subject at the beginning of the semester, apost-lesson survey after the game or regular lesson, and apost-lesson quiz with separate questions to assesssurface learning anddeep learning . Results .Enjoyment correlated with improvements indeep learning in both thegame and non-game classes.Games increased reportedenjoyment levels, especially in subjects where students reported the greatest anxiety aboutlearning, and this increase inenjoyment correlated positively with improvements indeep learning andhigher-order thinking . These results may have particular impact on non-traditional students. Conclusion . Whilefurther investigation is necessary to assess the specific affordances and long-term effects of GBL in higher education, this study offerspreliminary support for the claim thatGBL can improvedeep learning in this setting, by increasingenjoyment .